PENYULUHAN ALAT KONTRASEPSI IUD KEPADA PASANGAN USIA SUBUR DI DESA PUDUN JAE KECAMATAN PADANGSIDIMPUAN BATUNADUA - Harahap, Dewani (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
The rate of population growth that cannot be controlled has resulted in many impacts on the population, such as suffering from lack of food and nutrition, resulting in poor health, low education, and many unemployed people. Programs carried out by the government to reduce the rate of population growth can be carried out through the Family Planning movement and the voluntary use of contraceptives for couples of childbearing age (PUS). The government's policy on family planning currently leads to the use of long-term contraceptive methods (MKJP) such as the Intra Uterine Device (IUD). The purpose of this community service activity is so that couples of childbearing age can increase knowledge about IUD contraceptives as pregnancy prevention protection. Counseling is carried out using leaflets. The population and sample of this service are couples of childbearing age as many as 15 people. This activity was carried out at the Pudun Jae Village Hall. The results of this community service were enthusiastically received by the participants as seen from the number of couples who asked about information on the IUD contraceptive device, installation procedures, contraindications, advantages and disadvantages of using this contraceptive device in the IUD. It is recommended that outreach activities in increasing knowledge about IUD contraception can be carried out regularly with a more frequent frequency and the range of information dissemination can also be extended to families in general so that everyone, families and the community better know, understand about IUD contraceptives as pregnancy prevention protection.